Macroevolution - Wells, Richard J.; Nash, Robert D.; Coastline Community College (Olathe : RMI Media Productions, 1996)
You will go on a journey through time to witness the birth of our planet and life as we know it. Paleontologists discuss their use of fossils and other techniques to bring the macroevolutionary puzzle together. Also covered are ways in which scientists reconstuct those events leading to the formation of amino acids and the first unicellular organisms
VHS format
Keywords: Biology